MENJUAL BASUKI TJAHAJA PURNAMA LEWAT “TEMAN AHOK FAIR”: Strategi Kehumasan Pemasaran Komunitas Teman Ahok Menjelang Pemilihan Gubernur DKI Jakarta 2017 - Hutauruk, Mailan Fransian Cahyani (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2016)
Teman Ahok is a community who has goals to organized support for Basuki Tjahja Purnama (Ahok) on Governatorial Election DKI Jakarta 2017. Teman Ahok using personal brand Ahok to reach out their objective and applying marketing public relations strategy. By using qualitative research with case study approach implementation special event “Teman Ahok Fair”, this research aims to know process, channel communication as a marketing public relations tactics, to know how implementations and success special event “Teman Ahok Fair” which influence by community and volunteer, and to know affect personal brand Basuki Tjahja to Teman Ahok. The data is collected by doing deep interview and document tracking. This study results show that Teman Ahok can achieve marketing objectives by using public relations tools and collecting one million indetity of DKI Jakarta`s citizen. Teman Ahok achieve special event objectives because the power of community. Teman Ahok gets public and media attention because Ahok have a strong personal brand.